Aluminum-magnesium composite material with three-dimensional interlocking interface structure and preparation method of aluminum-magnesium composite material
By designing the interlayer of the three-dimensional structure at the interface of the aluminum/magnesium composite, the problem of low interface bonding quality caused by brittle intermetallic compounds is solved, the interface bonding force and mechanical properties are improved, and the interface structure of the aluminum/magnesium composite is realized. Performance optimization.
Patent Information
- Application Number
- CN202411174488.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
Aluminum/magnesium composites are prone to form brittle intermetallic compounds during the connection process, resulting in low quality of interface bonding and hindering its application development.
The intermediate layer of a three-dimensional structure is designed at the interface, and the load is distributed and the contact area is increased through metallurgy and mechanical combination, which prevents the formation of brittle intermetallic compounds and improves the interface binding force.
The interface structure performance of aluminum/magnesium composite materials has been improved, and the interface shear strength and mechanical properties have been significantly improved.
Smart Images

Figure CN119116481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium-magnesium composite material with a three-dimensional interlocking interface structure and a preparation method thereof; and belongs to the field of metal materials. Technical Background
[0002] Aluminum alloy and magnesium alloy are two of the most typical lightweight metal structural materials. In the current context of energy conservation and lightweight structure, the application proportion of these two alloys is increasing year by year. Aluminum alloy has excellent properties such as good strength, plasticity and corrosion resistance, while magnesium alloy has higher specific strength, which can greatly reduce the density of metal structural parts, but the corrosion resistance of magnesium alloy and other issues have largely restricted its development. Therefore, aluminum / magnesium bimetallic composite materials that combine the excellent properties of both have become a current research hotspot. However, during the connection process, the aluminum / magnesium interface is very easy to react and form brittle intermetallic compounds that are difficult to control, resulting in low interface bonding quality, which has become the biggest obstacle to the application of aluminum / magnesium composite materials. Introducing an intermediate layer as a medium to connect aluminum alloy and magnesium alloy can enhance the interface bonding strength, but the enhancement is limited.
[0003] The present invention converts the plane loading state of the interface into a three-dimensional loading state by designing a three-dimensional structure at the interface, so that the interface load is distributed to the substrates on both sides to a certain extent. When the metallurgical bonding between the middle layer and the metals on both sides is weak, mechanical bonding force can be introduced to achieve a higher interface bonding force. Summary of the invention
[0004] The present invention aims to solve the problem of poor interface performance caused by brittle intermetallic compounds generated during the composite process of aluminum alloy and magnesium alloy. By designing an intermediate layer with a three-dimensional structure at the interface, mechanical bonding force is introduced at the interface while preventing the generation of brittle intermetallic compounds, and the contact area at the interface is increased, ultimately obtaining an aluminum / magnesium composite material with excellent interface structure and performance.
[0005] The present invention provides an aluminum-magnesium composite material with a three-dimensional interlocking interface structure, characterized in that: the aluminum / magnesium layered composite material includes an A layer, a B layer, and a C layer, the A layer is pure aluminum or an aluminum alloy, the B layer is a composite of a metal foil and a metal mesh, or the B layer is a composite of a metal plate and a metal mesh, and is located between the A layer and the C layer, the C layer is pure magnesium or a magnesium alloy, the A layer and the B layer form a metallurgical bond and a mechanical bond, and the B layer and the C layer also form a metallurgical and mechanical bond, and the material of the B layer is selected from at least one of titanium, nickel, copper, iron, zinc, molybdenum, chromium, gold, silver, tin and their corresponding alloys.
[0006] Preferably, during the composite process of layer A, layer B and layer C, the layer B material can form an intermetallic compound or solid solution with the layer A material and / or the magnesium alloy, but the layer B material does not melt. Preferably, the layer B material is titanium, titanium alloy, nickel, nickel alloy, copper and copper alloy.
[0007] Preferably, the mesh number of the metal mesh of layer B is 30-500 meshes, the number of layers of the metal mesh is 1-5 layers, preferably 1 layer; the thickness of the metal foil of layer B is above 20 μm, and the thickness of the metal plate is above 20 μm.
[0008] In the present invention, the aluminum alloy of the A layer and the magnesium alloy of the C layer can be prepared by methods such as casting, deformation, 3D printing or powder metallurgy.
[0009] In the present invention, the material of the metal mesh / metal foil / metal plate of layer B can be titanium and titanium alloys, nickel and nickel alloys, copper and copper alloys, etc., which can form a certain metallurgical bond with aluminum alloys and magnesium alloys, and the melting point is higher than the eutectic liquid phase temperature point with aluminum alloys or magnesium alloys. The mesh size range is between 30 mesh and 500 mesh (preferably 60-200 mesh), and can be prepared by plain weave, twill weave, stranding or mesh punching methods, and the number of layers is between 1 and 5; the thickness of the metal foil / metal plate of layer B is above 20μm to ensure that it can play a partition role in the middle to prevent the eutectic reaction of aluminum alloys and magnesium alloys. For some situations where a thin middle layer is not required, a thicker plate material can be used instead of a foil.
[0010] Preferably, the structure of layer B is selected from at least one of a metal mesh / metal foil structure, a metal mesh / metal foil / metal mesh structure, a metal mesh / metal plate structure, and a metal mesh / metal plate / metal mesh structure.
[0011] Preferably, the thickness of layer B is 0.202-0.6 mm, preferably 0.21-0.45 mm.
[0012] The present invention provides a method for preparing an aluminum-magnesium layered composite material having a three-dimensional interlocking interface structure, the method comprising the following steps:
[0013] Step 1: After grinding and polishing the surface of the metal foil, lay a layer of metal mesh on both sides of the metal foil, and then place it in the mold. Or after grinding and polishing the surface of the metal foil, lay a layer of metal mesh on both sides of the metal plate, and then place it in the mold.
[0014] Step 2: placing the mold into a sintering furnace, performing pressure sintering under vacuum conditions, and compounding the metal mesh / metal foil / metal mesh together to obtain a mesh / foil / mesh composite middle layer; or placing the mold into a sintering furnace, performing pressure sintering under vacuum conditions, and compounding the metal mesh / metal plate / metal mesh together to obtain a mesh / plate / mesh composite middle layer;
[0015] Step 3: After the aluminum alloy and magnesium alloy are polished, they are placed in a mold and pressure-sintered with the composite mesh / foil / mesh intermediate layer, so that the mesh is embedded in the aluminum alloy and magnesium alloy matrix on both sides to form an aluminum alloy / magnesium alloy composite material with a three-dimensional interlocking interface structure; or
[0016] After the aluminum alloy and magnesium alloy are polished, they are placed in a mold and pressure-sintered with the composite mesh / plate / mesh intermediate layer, so that the mesh is embedded in the aluminum alloy and magnesium alloy matrix on both sides to form an aluminum alloy / magnesium alloy composite material with a three-dimensional interlocking interface structure;
[0017] The pressure sintering temperature ranges from 450°C to 600°C, preferably from 510 to 560°C, and more preferably from 540 to 560°C. The pressure ranges from 0.1 MPa to 30 MPa, and preferably from 8 to 12 MPa.
[0018] The present invention provides a method for preparing a titanium-magnesium layered composite material with a three-dimensional interlocking interface structure. The mold material used in step one includes materials such as aluminum oxide and zirconium oxide that do not react significantly with titanium alloys and magnesium alloys. If a slight reaction occurs, the reaction layer needs to be removed by grinding or pickling.
[0019] Preferably, in the method for preparing a titanium-magnesium layered composite material having a three-dimensional interlocking interface structure of the present invention, in step 2, the vacuum condition refers to the gas pressure in the sintering furnace being less than 10Pa, more preferably the gas pressure in the furnace being less than 1Pa.
[0020] Preferably, the present invention provides a method for preparing a titanium-magnesium layered composite material with a three-dimensional interlocking interface structure. In step 2, the pressure sintering process is: first increase the temperature to the sintering temperature at a heating rate of 1-20°C / min, and keep warm for 0.5-3 hours. The pressure sintering temperature range is 0.5-0.9 times the melting point of the intermediate layer metal. For example, if titanium alloy is used as the intermediate layer, the sintering temperature range is preferably 500°C-600°C, further preferably 510-560°C, and further preferably 540-560°C. The pressure range is 0.01MPa-20MPa, preferably 8-12MPa. The pressure is provided by a uniaxial hydraulic system attached to the hot press furnace, and the pressurizing direction is perpendicular to the interface direction.
[0021] The intermediate layer structure of metal mesh / metal foil / metal mesh can be adjusted to metal mesh / metal foil as needed. For example, if a strong metallurgical bond can be achieved between the base metal and the intermediate layer metal on one side, a three-dimensional interface structure may not be introduced on this side. For example, when the intermediate layer is Ni and its alloy, the metallurgical bond between Al and Ni is very strong, and only the Ni mesh needs to be introduced on the Mg side to enhance the interface bonding strength through a three-dimensional interlocking structure. However, when applied in industry, it is recommended to adopt an intermediate layer structure of metal mesh / M / metal mesh; the M is a metal foil or a metal plate.
[0022] The thickness of the aluminum alloy and the magnesium alloy in step 3 is above 0.1 mm.
[0023] Preferably, in step three, the pressure sintering process is: first increase the temperature to the sintering temperature at a heating rate of 1-20°C / min, and keep warm for 0.5-3 hours. The pressure sintering temperature range is preferably 510-560°C, more preferably 540-560°C, and the pressure range is 0.1MPa-30MPa, preferably 8-12MPa.
[0024] The interface tensile strength of the titanium-magnesium layered composite obtained in step 3 is 80-110 MPa, and the room temperature shear strength is 90-110 MPa.
[0025] Preferably, in step three, before pressure sintering, the furnace is first evacuated to a pressure less than 10 Pa.
[0026] The present invention introduces a mesh structure into the middle layer, and cooperates with the middle layer sintering and composite sintering processes, so that the interface shear strength of the product is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Attached Figure 1 The interface structure of the aluminum-magnesium composite material obtained in Example 1;
[0028] Attached Figure 2 This is the interface structure of the aluminum-magnesium composite material obtained in Example 2. DETAILED DESCRIPTION
[0029] Example 1
[0030] The aluminum-magnesium composite material with a three-dimensional interlocking interface structure of this embodiment is prepared according to the following steps:
[0031] Step 1: After grinding and polishing the surface of the pure Ti foil with a thickness of 100 μm, a layer of pure Ti mesh with a mesh number of 100 and a wire diameter of 0.15 mm is laid on both sides of the metal foil, and then placed in the mold.
[0032] Step 2: Place the mold into a sintering furnace and perform pressure sintering under vacuum conditions (the air pressure in the sintering furnace is less than 10Pa, provided by a uniaxial hydraulic system attached to the hot press furnace, the pressurizing direction is perpendicular to the interface direction, the pressurizing pressure is 10MPa, the sintering temperature is 550°C, and the sintering time is 60min), and the Ti mesh / Ti foil / Ti mesh are compounded together to obtain a composite intermediate layer with a thickness of 0.33mm, and its surface is polished and cleaned.
[0033] Step 3: Place 2A12 aluminum alloy and AZ31 magnesium alloy (both with a thickness of 30 mm) in a mold after surface polishing, and pressure sinter with the composite Ti mesh / Ti foil / Ti mesh intermediate layer, so that the mesh is embedded in the aluminum alloy and magnesium alloy matrix on both sides to form an aluminum alloy / magnesium alloy composite material with a three-dimensional interlocking interface structure. The pressure sintering temperature range is 550°C, the pressure is 10MPa, and the time is 60min.
[0034] The obtained aluminum-magnesium composite material has dense interface structure, good mechanical properties and a shear strength of 110 MPa.
[0035] Example 2
[0036] Other conditions were consistent with those in Example 1, except that the mesh size of the Ti mesh used was 80 meshes; the interface shear strength of the obtained aluminum-magnesium composite material was 105 MPa.
[0037] Example 3
[0038] Other conditions are consistent with those in Example 1, except that the sintering temperature is 500° C. At this time, the pores between the magnesium alloy matrix and the intermediate layer are not completely eliminated, and complete densification cannot be achieved; the interface shear strength of the obtained aluminum-magnesium composite material is 51 MPa.
[0039] Example 4
[0040] Other conditions are consistent with those in Example 1, except that the magnesium alloy used is AZ31 magnesium alloy green body, and sintering and densification are simultaneously performed during the interface composite process; the interface shear strength of the obtained aluminum-magnesium composite material is 112 MPa.
[0041] Example 5
[0042] Other conditions are the same as those in Example 1, except that:
[0043] The material of the middle layer is Ni mesh / Ni foil / Ni mesh (Ni mesh 100 mesh, wire diameter 0.15mm). Since the eutectic temperature of Ni and Mg is relatively low, a low-melting eutectic liquid phase is easily formed during the composite process. In order to avoid the formation of the liquid phase, the sintering temperature is reduced to 510°C (the sintering temperature of step 3). The interface shear strength of the obtained aluminum-magnesium composite material is 76MPa.
[0044] Comparative Example 1
[0045] Other conditions were consistent with those in Example 1, except that the intermediate layer did not use Ti mesh but only Ti foil; the shear strength of the obtained aluminum-magnesium composite material was 19 MPa.
[0046] Comparative Example 2
[0047] Other conditions are consistent with those in Example 1, except that no intermediate layer is introduced, and the aluminum alloy and the magnesium alloy are directly diffused and bonded. In order to avoid the formation of a low-melting-point aluminum-magnesium eutectic liquid phase during the composite process, the composite temperature is 420°C and the shear strength of the interface is 22 MPa.
[0048] Comparative Example 3
[0049] Other conditions were consistent with those in Example 4, except that the Ni mesh was not introduced into the middle layer, and only Ni foil was used as the middle layer. The shear strength of the obtained composite material was 57 MPa.
Claims
1. An aluminum-magnesium composite material with a three-dimensional interlocking interface structure, Features: The aluminum / magnesium layered composite material includes layer A, layer B, and layer C, wherein layer A is pure aluminum or aluminum alloy, layer B is a composite of metal foil and metal mesh, or layer B is a composite of metal plate and metal mesh, and is located between layer A and layer C, layer C is pure magnesium or magnesium alloy, layer A forms a metallurgical bond and a mechanical bond with layer B, and layer B also forms a metallurgical bond and a mechanical bond with layer C, and the material of layer B is selected from at least one of titanium, titanium alloy, nickel, nickel alloy, copper, copper alloy, etc.
2. A titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 1; Features: During the composite process of the A layer, the B layer and the C layer, the B layer material can form an intermetallic compound or a solid solution with the A layer material and / or the magnesium alloy, but the B layer material does not melt.
3. A titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 1; Features: The mesh number of the B layer metal mesh is 30 to 500 meshes, and the number of layers of the metal mesh is 1 to 5; the thickness of the metal foil of the B layer is above 20 μm, and the thickness of the metal plate is above 20 μm.
4. A titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 1; Features: The structure of layer B is selected from at least one of a metal mesh / metal foil structure, a metal mesh / metal foil / metal mesh structure, a metal mesh / metal plate structure, and a metal mesh / metal plate / metal mesh structure.
5. A method for preparing an aluminum-magnesium layered composite material having a three-dimensional interlocking interface structure, It is characterized in that The method comprises the following steps: Step 1: After grinding and polishing the surface of the metal foil, lay a layer of metal mesh on both sides of the metal foil and then place it in the mold. or After the surface of the metal plate is polished, a layer of metal mesh is laid on both sides of the metal plate, and then placed in the mold. or After the surface of the metal foil is polished, a layer of metal mesh is laid on one side of the metal foil and then placed in the mold. or After the surface of the metal plate is polished, a layer of metal mesh is laid on both sides of the metal plate, and then placed in the mold. Step 2: placing the mold into a sintering furnace, performing pressure sintering under vacuum conditions, and compounding the metal mesh / metal foil / metal mesh together to obtain a mesh / foil / mesh composite middle layer; or placing the mold into a sintering furnace, performing pressure sintering under vacuum conditions, and compounding the metal mesh / metal plate / metal mesh together to obtain a mesh / plate / mesh composite middle layer; Step 3: After the aluminum alloy and magnesium alloy are polished, they are placed in a mold and pressure-sintered with the composite mesh / foil / mesh intermediate layer, so that the mesh is embedded in the aluminum alloy and magnesium alloy matrix on both sides to form an aluminum alloy / magnesium alloy composite material with a three-dimensional interlocking interface structure; or After the aluminum alloy and magnesium alloy are polished, they are placed in a mold and pressure-sintered with the composite mesh / plate / mesh intermediate layer, so that the mesh is embedded in the aluminum alloy and magnesium alloy matrix on both sides to form an aluminum alloy / magnesium alloy composite material with a three-dimensional interlocking interface structure; The pressure sintering temperature ranges from 450°C to 600°C, preferably from 510 to 560°C, and more preferably from 540 to 560°C. The pressure ranges from 0.1 MPa to 30 MPa, and preferably from 8 to 12 MPa.
6. A method for preparing a titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 5, Features: The vacuum condition refers to the pressure in the sintering furnace being less than 1×10 -1 Pa, and more preferably the furnace pressure is less than 1.0×10 -2 Pa.
7. The method for preparing a titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 5, Features: In step 2, the pressure sintering process is: first increase the temperature to the sintering temperature at a heating rate of 1-20°C / min, and keep it warm for 0.5-3 hours. The pressure sintering temperature range is 0.5-0.9 times the melting point of the intermediate layer metal, preferably 500°C-600°C, further preferably 510-560°C, and further preferably 540-560°C. The pressure range is 0.01MPa-20MPa, preferably 8-12MPa.
8. The method for preparing a titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 5, Features: In step three, the pressure sintering process is: firstly, the temperature is raised to the sintering temperature at a heating rate of 1-20°C / min, and then kept at the temperature for 0.5-3 hours.
9. The method for preparing a titanium-magnesium layered composite material having a three-dimensional interlocking interface structure according to claim 5, Features: The interface tensile strength of the obtained titanium-magnesium layered composite is 80-110 MPa, and the room temperature shear strength is 90-110 MPa.
Citation Information
Patent Citations
Aluminum-magnesium layered composite material added with middle layer and preparation method of aluminum-magnesium layered composite material
CN114769587A
Preparation method of Ni intermediate layer reinforced magnesium-aluminum composite plate and magnesium-aluminum composite plate
CN118342863A
Titanium alloy net interpenetration enhancing magnesium-based composite board
CN204263643U
Cited By
Preparation method of aluminum / magnesium composite material added with composite middle layer
CN120245532A
A method for preparing an aluminum / magnesium composite material with an added composite interlayer
CN120245532B
